Analisis Akuntabilitas dan Transparansi Pengelolaan Zakat, Infak dan Sedekah (ZIS) (Studi Kasus Baznas Kota Payakumbuh) - Rifani Rifani; Muhammad Taufiq; Anwar Sholihin (ITB AAS INDONESIA Surakarta, 2023)
The main problem in this thesis is the implementation of the principles of accountability and transparency in the management of zakat, infaq and alms of the Payakumbuh City Amil Zakat Agency (BAZNAS) and their implications for BAZNAS performance. Payakumbuh and its implications for the performance of BAZNAS. The type of research used is qualitative research, by adopting case study research. The case in BAZNAS Payakumbuh City is that in 2020 the amount of zakat that can be collected is 2.1 billion rupiahs, while the potential for zakat in Payakumbuh City reaches 6.1 billion rupiahs annually. Data collection techniques used are through observation, interviews and documentation. Data processing was carried out in a qualitative descriptive manner, then described and classified aspects of certain problems and explained through effective sentences. From the research that the authors conducted in the field, it can be concluded that BAZNAS Payakumbuh City has implemented the principle of accountability in managing ZIS funds in accordance with the concept developed by Indonesia Magnifence of Zakat (2011) both in the decision-making process and in the process of policy outreach. Furthermore, the principle of transparency carried out by BAZNAS Payakumbuh City has not fully implemented the principle of transparency. Presentation of information as a whole has not been carried out by BAZNAS Payakumbuh City. As well as proposals that are received, whether they are acceded or not, they have not been published digitally on social media, so mustahiq have to come back and forth to the office to ask how far the submission process is. Currently, of the five indicators of transparency principles, there are two transparency principles that have not been fully implemented by BAZNAS Payakumbuh, namely the publication of balance sheets and sharia audits. This research still shows 'mix results' regarding the impact of implementing accountability and transparency on BAZNAS performance. Data shows that from 2017 to 2020 the implementation of the principles of accountability and transparency had a negative impact with a decrease in collection performance in 2018. However, in 2017 it showed contradictory results. The explanation for this contradictory result is that there has been a change in regulation that ASN zakat at the high school and university levels is managed by the Provincial BAZNAS.